2012
DOI: 10.1080/10803548.2012.11076949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ergonomic and Occupational Health-Related Problems Among Female Prawn Seed Collectors of Sunderbans, West Bengal, India

Abstract: Sixty female prawn seed collectors and 60 female control subjects from Sajenakhali andmusculoskeletal disorders physiological stress prawn seed collectors hand grip strength rapid entire body assessment (REBA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
7
15
0
Order By: Relevance
“…Therefore, the heart has to beat faster to supply more blood to the muscle to provide energy. The present findings are supported by the findings of Guyton 36) , who also emphasized that stretching of muscles caused vasoconstriction in the muscles, which resulted in restriction of blood flow and in turn increased systolic blood pressure. The physiological parameters (heart rate and blood pressure) of the experimental subjects were also increased just after completion of work due to performance of highly repetitive actions during work (spading, planting seeds and sprinkling water) and high environmental temperature (especially when picking crops and carrying crops).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the heart has to beat faster to supply more blood to the muscle to provide energy. The present findings are supported by the findings of Guyton 36) , who also emphasized that stretching of muscles caused vasoconstriction in the muscles, which resulted in restriction of blood flow and in turn increased systolic blood pressure. The physiological parameters (heart rate and blood pressure) of the experimental subjects were also increased just after completion of work due to performance of highly repetitive actions during work (spading, planting seeds and sprinkling water) and high environmental temperature (especially when picking crops and carrying crops).…”
Section: Discussionsupporting
confidence: 90%
“…This study also supports the fact that low back pain represents the most common and most expensive MSD experienced in the workplace. This result corroborates with the work of Das et al 23 According to them, musculoskeletal disorders (MSDs) have been positively associated with constant awkward bending postures for prolonged period of time. This study also revealed that female brick field workers suffered more discomfort feeling than male workers.…”
Section: Commentssupporting
confidence: 92%
“…This study also revealed that female brick field workers suffered more discomfort feeling than male workers. This result was supported by Das et al, 23 they found in other studies that female workers suffered more discomfort feeling than male workers because they perform extra hand-intensive jobs in their home also, which is another causative factor for more discomfort feeling (pain). This study also shows that, among the brick field workers reporting subjective discomfort, most of them felt pain, followed by tingling and numbness in their hands.…”
Section: Commentssupporting
confidence: 66%
“…If brick field workers are constantly engaged in hand-intensive jobs, they may be affected by discomfort (pain) in the upper extremities and significant changes in the hand-grip strength [19]. This result also corroborates with the work of Das et al [20] and Alperovitch-Najenson et al [21] who suggest that workers, constantly engaged in hand-intensive jobs, are likely to suffer from upper limbs MSDs. Our results revealed that the decreased hand-grip strength may be related to increased loading at the proximal end, that is, muscles at the cervical spine and shoulder joints may have to exert greater forces in order to control the arm movements.…”
Section: O R I G I N a L P A P E R B Das Ijomeh 2014;27(3)supporting
confidence: 80%